1998
DOI: 10.1590/s0103-50531998000500017
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Selective Electrode for the Determination of Iron(III) in Vitamin Formulations

Abstract: Construiu-se um eletrodo íon-seletivo de grafite-epoxi recoberto para Fe(III), baseado no par-iônico formado entre o ânion [Fe(citrato)2] 3e o cátion tricaprililmetilamônio (Aliquat 336) incorporado em uma matriz de PVC (cloreto de polivinila). Uma membrana fina foi preparada pela incorporação deste par-iônico, ftalato de dibutila (DBPh) em PVC e aplicados diretamente em um tubo Perspex® contendo o condutor de grafite-epoxi. A solução de recobrimento foi preparada pela dissolução de 30% (m/m) de PVC em 10 mL d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…The DubininRadushkevich equation was used to calculate the characteristic energy of adsorption, E 0 (Boehm 1966) and with this the parameter L 0 is calculated. The acidic and basic surface groups were determined according to the method of Boehm (Teixeira et al 1998). One gram of carbon sample was placed in 50 ml of 0.05 N solutions of either sodium hydroxide or hydrochloric acid.…”
Section: Methodsmentioning
confidence: 99%
“…The DubininRadushkevich equation was used to calculate the characteristic energy of adsorption, E 0 (Boehm 1966) and with this the parameter L 0 is calculated. The acidic and basic surface groups were determined according to the method of Boehm (Teixeira et al 1998). One gram of carbon sample was placed in 50 ml of 0.05 N solutions of either sodium hydroxide or hydrochloric acid.…”
Section: Methodsmentioning
confidence: 99%
“…17 The construction of a hydrogen ion-selective potentiometric electrode based on a tridodecylamine ionophore dispersed in a poly(vinylchloride) (PVC) membrane, 18,19 or poly(1-aminoanthracene) films 20 has been described. In addition, Rodwedder et al 21 and Fatibello and co-workers [22][23][24][25] have shown the use of coated graphite epoxy ion selective electrodes for determinaton of cations using ion-pair formation with tricaprylylmethylammonium cation in a PVC matrix. Using a similar system with incorporation of saccharinate anion and toluidine, Rover et al 26 have described the construction of a tubular ion selective electrode useful for determination of saccharin.…”
Section: Potentiometric Sensorsmentioning
confidence: 99%
“…Repeated monitoring of the potential on the same portion of the sample (1 × 10 -3 M) gave a standard deviation of ± 2 mV and there was no significant change in the slope. It is interesting to note that the electrode in our present work gave a quicker response time of 15 s with stable reading and works over a lower concentration range of Fe(III) ions as compared to ion-selective electrode developed earlier for Fe(III) (Teixeira et al 1998;Sil et al 2005).…”
Section: Response Time and Lifetime Of Membrane Electrodementioning
confidence: 61%
“…Although iron is an essential element to all forms of life, biologically, it plays an important role in oxygen and electron transport and provides fundamental structure of myoglobin, hemoglobin, hemenzymes and many cofactors involved in enzyme activities. Approximately 10-15 mg of iron is present in the food ingested during a day (Teixeira et al 1998). The absence of iron in the organism causes anemia which results decreased red blood cell content.…”
Section: Introductionmentioning
confidence: 99%